Bedside Endoscopic Ultrasound in Critically Ill patients. (6th June 2011) - Mohamadnejad, Mehdi; LeBlanc, Julia K.; Sherman, Stuart; Al-Haddad, Mohammad; McHenry, Lee; Cote, Gregory A.; DeWitt, John M.
Abstract : Background . The aim of this study was to evaluate the role and impact of EUS in the management of critically ill patients. Methods . We retrospectively identified all patients at our institution over a 68-month period in whom bedside inpatient EUS was performed. EUS was considered to have a significant impact if a new diagnosis was established and/or the findings altered subsequent clinical management. Results . Fifteen patients (9 male; mean age58 ± 15 years) underwent bedside EUS without complications. EUS-FNA (median 4 passes; range 2–7) performed in 12 (80%) demonstrated a malignant mediastinal mass/lymph node (5), pancreatic abscess (1), excluded a pelvic abscess (1), established enlarged gastric folds as benign (1) and excluded malignancy in enlarged mediastinal (1) and porta hepatis adenopathy (1). In two patients, EUS-FNA failed to diagnose mediastinal histoplasmosis (1) and a hemorrhagic pancreatic pseudocyst (1). In three diagnostic exams without FNA, EUS correctly excluded choledocholithaisis (n = 1 ) and cholangiocarcinoma (1), and found gastric varices successfully thrombosed after previous cyanoacrylate injection (1). EUS was considered to have an impact in 13/15 (87%) patients. Conclusions . In this series, bedside EUS in critically ill patients was technically feasible, safe and had a major impact on the majority of patients.